The Accounting Measurement on Agricultural Activities Based on Financial Reporting Standards (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:          The research aimed to show how IFRS affect the provision of financial information to agricultural companies and its impact on the final financial reports that reflect the company's performance, as agricultural companies are considered one of the most important economic sectors in many countries, as they include a variety of activities such as crop cultivation, livestock breeding, forestry and fishing activities, etc., and it is important that the financial information provided about these companies is accurate and reliable, allowing investors, shareholders and regulators to understand the financial situation. Companies in the local environment rely on the requirements of the unified accounting system and its instructions and on the local accounting rules issued by the Accounting and Control Standards Board in Iraq when preparing their financial statements, which led to these companies facing challenges with regard to the accounting measurement of biological assets due to the changing nature of those assets in addition to the impact of natural and climatic factors on these assets, and the accounting measurement of biological assets requires determining their fair value and estimating the expected return and cost of them Gross, in addition to estimating potential losses as a result of risks related to agricultural factors, therefore, the selection and application of appropriate accounting policies can significantly affect the final financial results of agricultural companies.